2019
DOI: 10.3390/en12101837
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Protection Scheme for DC Grid Based on the Half Bridge Modular Multilevel Converter System

Abstract: The half bridge (HB) modular multilevel converter (MMC) technology is considered a breakthrough to mitigate the shortcomings of the conventional voltage source converter (VSC) in high-voltage direct-current (HVDC) grid application. However, interruption of the DC fault is still a challenge due to fast di/dt and extremely high levels of DC fault current. The fault interruption using a DC circuit breaker (DCCB) causes enormous energy dissipation and voltage stress across the DCCB. Therefore, the use of a fault c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…It has no resistance in its superconducting state and, therefore, does not impede the flow of normal current. Additionally, the fault current is limited within about 2 ms through quenching when the critical point of the superconductor is exceeded by the fault current, thereby limiting the growth of the fault current [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. To respond quickly and safely to DC transients, we researched superconductor and mechanical DC cutoff technology and proposed a hybrid superconducting DC circuit breaker [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It has no resistance in its superconducting state and, therefore, does not impede the flow of normal current. Additionally, the fault current is limited within about 2 ms through quenching when the critical point of the superconductor is exceeded by the fault current, thereby limiting the growth of the fault current [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. To respond quickly and safely to DC transients, we researched superconductor and mechanical DC cutoff technology and proposed a hybrid superconducting DC circuit breaker [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…When SFCLs are combined with mechanical DCCBs, it will be easier to interrupt DC fault current because of the low power loss, low recovery voltage, high interrupting ability, and high reliability. Lee, Ho-Yun, et al showed the system recovery characteristics of resistive-type SFCL, saturated iron core SFCL and hybrid-type SFCL in combination with DCCBs by simulations [6]. The hybrid-type SFCL in combination with a DCCB has the best performance in interruption time, recovery time energy dissipation, and voltage transients.…”
Section: Introductionmentioning
confidence: 99%
“…Lee, Ho‐Yun, et al. showed the system recovery characteristics of resistive‐type SFCL, saturated iron core SFCL and hybrid‐type SFCL in combination with DCCBs by simulations [6]. The hybrid‐type SFCL in combination with a DCCB has the best performance in interruption time, recovery time energy dissipation, and voltage transients.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results showed that by comparing the specific performance indexes including the current-limiting ratio and restraining capability to voltage/power fluctuations, the R-SFCLs is more preferable than the inductive-type SFCL (I-SFCL) [2,3]. Lee et al studied fault interruption and system recovery characteristics considering three types of fault limiting devices such as an R-SFCL, a saturated iron core SFCL, and a hybrid-type SFCL in combination with DCCBs by simulations [4]. The simulation results showed that, among the three fault limiting devices, the hybrid-type SFCL in combination with a DCCB, delivers the most desirable performance in terms of interruption time, recovery time, energy dissipation, and voltage transients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al studied fault interruption and system recovery characteristics considering three types of fault limiting devices such as an R-SFCL, a saturated iron core SFCL, and a hybrid-type SFCL in combination with DCCBs by simulations [4]. The simulation results showed that, among the three fault limiting devices, the hybrid-type SFCL in combination with a DCCB, delivers the most desirable performance in terms of interruption time, recovery time, energy dissipation, and voltage transients [4]. Liang et al proposed a DC hybrid-type SFCL with a two-stage current-limiting capability [5,6].…”
Section: Introductionmentioning
confidence: 99%